Иностранный язык (английский). English for PhD students. Part 1 электронный курс - Зеремская, Ю. А. лингвист доцент Томского политехнического университета, кандидат филологических наук 1980- (TPU Moodle, 2023)
The course is intended for developing listening, reading, writing and speaking skills, revising grammar material and increasing vocabulary on the topics. The course covers such topics as Postgaraduate education, Doing postgraduate research, Writing PhD thesis и Research methods. The objective of the course is to develop postgraduate students' English language communicative competency at the level that will enable them to function adequately in scientific life and in their general professional activity.